Analysis on Sportsmanship as a Universal Value and Sportsmanship Orientations of Candidate National Athletes - Şirin Pepe; Arif Özsarı (Türk Spor ve Egzersiz Dergisi, 2021)
This study aimed to analyze the sportsmanship orientations of candidate national athletes in the context of sportsmanship as a universal value, and included a total of 95 athletes, with the age range of 18.11 ± 3.58, 54 of whom were female, while 41 were male, who were all selected to the athletic development camp of the national hockey team. Data were collected through the demographic form containing personal information and the ‘Multidimensional Sportsmanship Orientation Scale’ (MSOS) developed by Vallerand et al. (1997), and adapted into Turkish by Sezen-Balçıkanlı (2010). The results indicated that there was statistical significance in the sportsmanship orientation of candidate national hockey athletes as to gender, education level, and age range that sportsmanship values of female athletes were more prominent, and that athletes with a lower level of education, and less athletic experience as well as those who were at a younger age appeared to contribute to the sportsmanship values more positively in relation to complying with social norms, respecting rules and management, and adhering to responsibilities in sports, whereas those who were older and more experienced besides having higher education levels turned out to be more attentive in terms of respect for one’s opponents. Considering the mean values obtained from the research scale form, it can be assumed that the sportsmanship orientation of the candidate national athletes is at a remarkably good level. It is a fact that the positive behavior of national athletes will add a positive value to all humanity.